Magnetic properties and magnetocaloric effect in Dy100-xYx solid solutions - Sergey Taskaev; Vladimir Khovaylo; Maxim Ulyanov; Dmitriy Bataev; Anastasiya Basharova; Marina Kononova; Daniil Plakhotskiy; Mikhail Bogush; Dmitriy Zherebtsov; Zhang Hu (AIP Advances, 2021)
Dysprosium possesses the highest magnetic moment among the rare-earth elements and undergoes a second-order magnetic phase transition to a complex helical antiferromagnetic ordering at Néel temperature TN = 180 K which is followed by a transformation to the ferromagnetic ordering at a lower temperature. Superior magnetic properties and tunability of the magnetic phase transition temperatures make Dy and its solid solutions perspective for the use in technology of magnetic refrigeration at cryogenic temperatures, specifically for the liquefaction of natural gases. In this work we report on the evolution of magnetic properties in solid solutions of Dy100-xYx (x = 0 – 15). It was found that the dilution of Dy magnetic subsystem by a non-magnetic Y has rather a weak impact on the magnetization saturation, which decreases from Ms ∼280 A⋅m2/kg in the x = 0 sample to Ms ∼259 A⋅m2/kg in the x = 15 sample. As a consequence, the isothermal magnetic entropy change was found to decrease slightly in the series of Dy100-xYx (x = 0 – 15) solid solutions.